Tatalaksana Pasien di Rumah Sakit oleh Dokter Gigi dalam Pandemi COVID-19: Literature Review - Eghia Laditra Ambarani; Chriswardani Suryawati; Zahroh Shaluhiyah (Jurnal Manajemen Kesehatan Indonesia, 2022)
On March 12, 2020, WHO (World Health Organization) officially declared the COVID-19 as a pandemic with the spread of SARS-CoV-2 globally and caused thousands of deaths. The wide and very fast spread of COVID-19 and reports of its spread to health workers, dental professionals are at high risk of nosocomial infections and can be potential carriers of the disease. This study aims to analyze dental management carried out in various countries in the COVID-19 era. This study uses a simplified approach systematic review method. A total of 101 articles were found in the initial search. Based on the selection of article searches resulted in 11 articles consisting articles from international journals. The study resulted in the management of dentistry in the COVID-19 era being divided into four parts, namely online patient triage, in-office patient triage and clinics preparation, treatment management, and post-treatment management. This management had not been carried out before COVID-19, but with COVID-19 still going, having a safe dental management can be a useful lesson for dental professionals or hospital managers for future epidemics or pandemics.